GREEN GOOD GOVERNANCE: A CRITICAL ANALYSIS OF PAKISTAN’S FEDERAL POLICIES ON CLIMATE CHANGE - Muhammad Nawaz Masroor Alam Shah; Dr. Ahsan Riaz (Policy Research Journal, 2025)
Pakistan is a country which has been ranked fifth by the German climate risk index in terms of the vulnerability which climate change poses. The extreme environmental events such as unnatural periods of rain, fast melting of the glaciers, acidification of oceans, destruction of the coral reefs, biodiversity depletion and the rising levels of the sea in particular at unprecedented rate compels serious actions to be taken in relation to climate governance in Pakistan. Climate change has put the lives of millions of people at stake. People have been forced to migrate from one place to another in search of food, water, shelter and even to save their lives which is now being compromised with every passing day. The sensitivity of the issue is also evident from the fact that the office of the high commissioner of United Nations has already linked climate change with human right. Therefore, international institutions put several obligations on states which are to be followed in the context of climate governance. This research article aims to explore the federal policy of Pakistan by drawing a special emphasis on good governance, explicitly in the context of climate change. The research also analyzes and interprets coherence between international framework for green governance with Pakistan's policy narrative on it. Qualitative and analytical method of investigation will be carried out. The data will be collected from official policy reports published by Ministry of Climate Change of Pakistan. The published research articles in environmental journals and newspapers will also be considered for data collection and analysis. The findings of this research will allow government of Pakistan to adopt resilience and mitigation policies for sustainable development which will reflect the international standards.